Responsibility of Regional Disaster Management Agency through Institutional Coordination (BPBD study of North Luwu Regency) - Fajar, Fera Juliana; Fatmawati, Fatmawati; Malik, Ihyani (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The objective of this research to determine the institutional coordination in improving the effectiveness of the Regional Disaster Management Agency (BPBD); factors that can improve the effectiveness of BPBD; and obstacles and efforts to overcome obstacles in institutional coordination to improve BPBD. The research method used is a qualitative approach. The data source consists of primary data and secondary data. Data collection tools through observation, interviews and documentation studies. Technical analysis of data in this study using triangulation techniques as a technique to check the validity of the data. Institutional coordination in disaster management carried out by BPBDS with other agencies/Agencies (Department of Health, Social Services and Public Works Department of Spatial Planning and land), has been implemented quite well. Similarly, the observation shows that some indicators of coordination have been implemented well, but some are still lacking and some have not been implemented such as guidance, consultation and direction through official and routine meetings. Factors that influence coordination in improving the effectiveness of BPBDS are: differences in ways, work attitudes, duties, commitments, procedures, financing, inventory of infrastructure and supporting facilities, and abilities/skills. Obstacles encountered in coordination to improve the effectiveness of BPBD is the lack of communication and the intensity of the meeting, the persistence of egosectoral attitude and the ability of implementers in disaster management.